Design of a solar powered miniature water surface cleaning robot - Sagor, Md Asaduzzaman; Saha, Sanglap; Hasan, Rifat; Haque, Mazeedi (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.